The ways urban marginalized group conceptualizes health and wellbeing: The case of the waste pickers in Surabaya, Indonesia - Yohanes Kambaru Windi; Dyah Wijayanti; Eko Rustamaji Wiyatno (Universitas Udayana, 2020)
Background and purpose: Health and wellbeing have a different meaning for an individual, institution, ethnicity and organization. The study aims to overview the ways waste pickers conceptualize health and wellbeing. Methods: A qualitative procedure deployed to identify the predictors of health and wellbeing according to the waste pickers and how they perceive them. Forty waste pickers were involved as participants. Semi-structured in-depth interviews, natural group discussion (NGD) and casual conversation are the main methods for collecting information. The information was analysed using a thematic and inductive approach. Results: The waste pickers identify health as free from diseasesand illness, being able to work, a peaceful mind, positive relation within the family and social life, being grateful for life, surrender to God, and being happy. They relate wellbeing with gratefulness with achievements, sense of enough, being satisfied with life, submission to God, sense of “enough”, frugality and some assets back hometown. Conclusion: The study concludes that waste pickers provide apractical understanding of health and wellbeing. It recommendsthat understanding and measuring health and wellbeing should on the context of the target population.